Approximation of optimum retail location and design for urban lifestyle centers of Davao City based on consumer patronage probability - Arbotante, Samantha V. (2015)
From the historical agoras to the super regional shopping malls, shopping centers have evolved into different typologies with corresponding sizes and elements. Rising trend among them are the urban lifestyle centers (ULC). These centers value and prioritize local entrepreneurs with main features such as pocket gardens allotted for alfresco restaurants and other outdoor amenities. One of the greatest factors of success of businesses is the proper location. It must be accessible to the public, located in a commercial zone, and close to target market. This study used the Modified Huff Model of Retail Location which can predict consumer patronage probability of a center from a source target market area, competed with other centers. This study relies on the model which states retail attractiveness is directly proportional to increase of probability while increasing distance is inversely proportional to it. Retail attractiveness has several categories namely amenities, ambulance, atmospherics, food, macro-accessibility, merchandising, micro-accessibility, personal service, security, site parameters, specialty entertainment, and special event entertainment. For distance computations, focusing at the top 5 most populated barangays in Davao namely Buhangin, Maa, Sasa, Bucana, and Talomo. Their centroids are being calculated as point of origin. The survey was conducted on the main study areas. It is then discovered that Davaoenos and Tourists visit ULCs mainly for authentic local food, local shopping and for local entertainment. It was also found out that Ecoland has received highest consumer patronage probability among proposed locations for the new ULC. Today, all ULCs received a rating of low-priority among under retail attractiveness scale and further improvements using the said retail attractiveness categories as basis could increase consumer patronage probability.